The phylogeny and metabolic potentials of an n-alkane-degrading Venatorbacter bacterium isolated from deep-sea sediment of the Mariana Trench - Wang, Jiahua; Zhang, Yan; Liu, Ying; Xie, Zhe; Cao, Junwei; Zhang, Hongcai; Liu, Jie; Bao, Tianqiang; Sun, Congwen; Liu, Bilin; Wei, Yuli; Fang, Jiasong (Frontiers in Microbiology, 2023)
Recently, several reports showed that n-alkanes were abundant in the hadal zone, suggesting that n-alkanes could be an important source of nutrients for microorganisms in hadal ecosystems. Up to date, most of the published studies on microbial capacity to degrade hydrocarbons were conducted only at atmospheric temperature and pressure (0.1 MPa), and little is known about whether and which microbes could utilize n-alkanes at in-situ environmental conditions in the hadal zone, including low temperature and high hydrostatic pressure (especially >30 MPa). In this study, a piezotolerant bacterium, strain C2-1, was isolated from a Mariana Trench sediment at depth of 5,800 m. Strain C2-1 was able to grow at in-situ temperature (4 ℃) and pressure (58 MPa) with n-alkanes as the sole carbon source. Phylogenetically, strain C2-1 and related strains are classified into the genus Venatorbacter. Large-scale metagenomic analysis showed that Venatorbacter has a wide environmental distribution in seawater (38), marine sediments (3), hydrothermal vent plumes (2), Antarctic ice (1), groundwater (13), and marine sponge ecosystems (1). Most Venatorbacter species are non-obligate n-alkane degraders that could utilize, at a minimal, C16-C18 n-alkanes, as well as other different types of carbon substrates, including carbohydrates, amino acids, peptides, and phospholipids. The type II secretion system, extracellular proteases, phospholipase and endonuclease of Venatorbacter species were robustly expressed in the metatranscriptomes of deep-sea hydrothermal vents, suggesting their important contribution to secondary productivity by degrading extracellular macromolecules. Identification of denitrifying genes suggested a genus-specific ecological potential that allowed Venatorbacter species be active in anoxic environments, e.g., the oxygen-minimal zone (OMZ) and the deeply-buried marine sediments. Our results show that Venatorbacter species are responsible for degradation of hydrocarbon and extracellular macromolecules, suggesting that they may play an important role in the biogeochemistry process in the trench ecosystems.